2011
DOI: 10.2478/v10181-011-0058-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effectiveness of the microscopic method and the multiplex PCR method in identifying and discriminating the species of Nosema spp. spores in worker bees (Apis mellifera) from winter hive debris

Abstract: The objective of this study was to compare the effectiveness of the multiplex PCR method and traditional light microscopy in identifying and discriminating the species of Nosema spp. spores in worker bees from winter hive debris in the Province of Warmia and Mazury (NE Poland). A total of 1000 beesdead after from the bottom of the hive from bee colonies were analyzed. Spores were identified with the use of a light microscope (400-600x magnification). Spores were assigned to species by the multiplex PCR method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
4
14
0
Order By: Relevance
“…Duplex PCR confi rmed the presence of different microsporidia species in worker bees sampled from the same colony on different dates. The above results validate our previous observations [21] that worker bees infected with different Nosema species can inhabit the same colony [25]. Meana et al [26] also demonstrated that the origin of the sampled material plays an important role in the identifi cation of N. ceranae spores.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Duplex PCR confi rmed the presence of different microsporidia species in worker bees sampled from the same colony on different dates. The above results validate our previous observations [21] that worker bees infected with different Nosema species can inhabit the same colony [25]. Meana et al [26] also demonstrated that the origin of the sampled material plays an important role in the identifi cation of N. ceranae spores.…”
Section: Discussionsupporting
confidence: 80%
“…spores in HB from winter hive debris ranged from 13.74 x 10 4 in group N to 25.62 x 10 4 in group Cs (Table 1). The average number of Nosema spp.…”
Section: Resultsmentioning
confidence: 99%
“…Along with extensive studies on the determination of the species of Nosema spores at the molecular level in the world (23,32,33), the number of studies related to the agent for the disease seems to be high in Turkey; however, these studies have been limited to the general presence …”
Section: Discussionmentioning
confidence: 99%
“…Having used multiplex-PCR diagnosis for Nosema spores and different primer pairs targeting the rRNA gene for discrimination of the species, Michalczyk et al (23) reported that Nosema ceranae was the dominant species in European honeybees. Traver and Fell (24) studied 586 managed A. mellifera colonies from Virginia in 2009 using real-time PCR to detect Nosema apis and Nosema cerenea.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the obtained products was evaluated by comparison with the GeneRuler TM 100 bp 36 Ladder Plus (Fermentas) molecular size marker. Electrophoresis results were archived using the GelDoc (Bio-Rad) gel documentation system (Michalczyk et al, 2011).…”
Section: Methodsmentioning
confidence: 99%